Zvijezda hispanoameričkog pjesništva - Lovrenčić, Željka (Array, 2008)
Chilean poet, university professor and essayist of Croatian origin Andrés Morales Milohnić on 4 December 2007 became the youngest member of the Chilean Academy of Language, a prestigious institutions that has been active since 5 June 1885 and has 36 full members. Andrés, the son of a Spaniard father and a Croatian mother (the son of Visnja Milohnic Roje, also a writer, and grandchild of poet Ljubica Milohnić née Roje of Split) who fled Franco and Tito, was born in Santiago in 1962. He has a doctorate in literature and lectures at two universities: at the state-run Universidad de Chile and at the privately owned Diego Portales. He has to date published 15 collections of poetry and is considered one of the best young Hispano-American poets. A few of his collections are: Por ínsulas extrañas (On Strange Islands, 1982), Soliloquio de fuego (Soliloquy of Fire, 1984), Vicio de belleza (The Vice of Beauty, 1992), Romper los ojos (Destroy the Eyes, 1995), Antología personal (Personal Anthology, 2001), Memoria muerta (Dead Memory, 2003), Demonio de la nada (Demon of Oblivion, 2005) and many more. His works have been translated into eight languages and included in over 40 collections of poetry in Chile and abroad. His Selected Poems were released in Croatia in 2002 by publisher D.S.M. grafike, translated by Željka Lovrenčić and Jordan Jelić. Morales is the recipient of numerous top literary awards among which the most significant is the Pablo Neruda Award for 2001. He is one of the top promoters of Croatian culture in Chile and has tried his hand at translating: he joined Željka Lovrenčić in translating the book Poesía croata contemporánea (Contemporary Croatian Poetry, 1997) and Drago Štambuk's El viento de las estrellas oscuras (2003) from Croatian to Spanish.